Ọ̀rúnmìliàn Film-Philosophy : An African Philosophy through Cinematic Storytelling - Bello, Saheed Adesumbo; Studies, Bayreuth Academy of Advanced African (University of Bayreuth African Studies Working Papers, 2023)
This paper develops a film-philosophy, (which I call “Ọ̀rúnmìliàn film-philosophy”), by exploring and analyzing the praxis of Ọ̀rúnmìlà oral philosophy and narrative aesthetics in an African cinematic storytelling. It defends a modest thesis by using Saworoide (dir. Túndé Kèlání’s, 1999) as an example of how the African/Nigerian filmmakers are influenced by their inherited oral philosophical traditions. It argues that the condition of philosophy that gives “presence to non-presence” (so that the living can dialogue with the dead) and “knowledge to the unknown” (in order to heal and to re-moralize the living) is central to the Ọ̀rúnmìliàn film-philosophy. The central argument is based on what I call the Ọ̀rúnmìlà “parable of Eégún” (masquerade); and the film-philosophy finds some philosophical similarities in Stanley Cavell’s The World Viewed on the one hand, and Christopher Falzon’s concept of cinema as philosophy, (which is based on Plato’s parable of the cave), on the other. The paper therefore stresses the intercultural correlation between an African film-Philosophy and the modern European/western traditions of film-philosophy. It contributes to film and philosophy scholarship by exploring the manifestations of Yorùbá/Ọ̀rúnmìlà philosophical texts in the contemporary Nigerian film as case study of how contemporary African filmmakers, like their oral artiste counterparts, continue to articulate their inherited traditions via cinematic storytelling.
Keywords: Africa; Film; Philosophy; Storytelling; Ọ̀rúnmìlà; Yoruba